Recent advances in shear‐thinning and self‐healing hydrogels for biomedical applications - Uman, Selen; Dhand, Abhishek; Burdick, Jason A. (Journal of applied polymer science, 2020)
ABSTRACT Shear‐thinning and self‐healing hydrogels are being investigated in various biomedical applications including drug delivery, tissue engineering, and 3D bioprinting. Such hydrogels are formed through dynamic and reversible interactions between polymers or polypeptides that allow these shear‐thinning and self‐healing properties, including physical associations (e.g., hydrogen bonds, guest–host interactions, biorecognition motifs, hydrophobicity, electrostatics, and metal–ligand coordination) and dynamic covalent chemistry (e.g., Schiff base, oxime chemistry, disulfide bonds, and reversible Diels–Alder). Their shear‐thinning properties allow for injectability, as the hydrogel exhibits viscous flow under shear, and their self‐healing nature allows for stabilization when shear is removed. Hydrogels can be formulated as uniform polymer and polypeptide assemblies, as hydrogel nanocomposites, or in granular hydrogel form. This review focuses on recent advances in shear‐thinning and self‐healing hydrogels that are promising for biomedical applications. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48668.